Contribution of Sri Lanka for open access publishing : A picture from DOAJ - Navaneethakrishnan, S. (Faculty of Graduate Studies, University Kelaniya, 2014)
Within the context of Knowledge hub, current situation of Sri Lanka impels to find out new sources to boost up the visibility of academic findings of Sri Lankan scholars. Open access was identified as an alternative way to overcome this situation. Open access means publishing and allowing any user to search, download, read, copy, share, and comment the scholarly literature, freely on the Internet. Numerous studies have been carried out by scholars covering various aspects of open access publishing and several open access projects were implemented in Sri Lanka and all over the world. Objective of present study is to compare open access publishing trend of Sri Lanka with global trend during the period 2004-2013 as reflect in Directory of Open Access Journals (DOAJ) database considering coverage and comprehensiveness. To undertake the present study data has been retrieved from DOAJ on July 20th 2014. Quantitative method was used in this study and data has been tabulated and analyzed as per the defined objective. Findings of the study illustrate that DOAJ which on date of 20th July 2014 indexed 1,685,475 articles from 9911 journals on its website from 134 countries all across the globe. Contribution of Sri Lanka was 292 articles from 13 journals. Among the leading contributors of SAARC nations India ranked as first having 5.01% contributions followed by Pakistan (2.27%), Bangladesh (0.03), Sri Lanka (0.02), Bhutan (0.01) and Nepal (0.01). Sri Lanka's contribution to open access publishing through DOAJ database has fluctuated and drops with 0.03% during the later part of the study span. Overall share of Sri Lanka was 0.02%. If the trend continues, near future Sri Lanka may become least contributor of DOAJ among the SARRC nations. The main suggestion of this study was incorporating around 5000 articles from 54 journals indexed in SLJOL in the DOAJ, which will leads for an instant increase in the contribution of Sri Lanka by 0.02% to 0.29%. Further it will show the way to rank Sri Lanka as third leading contributor among the SAARC nations. (335 words)
Keywords: Open Access; Sri Lanka; DOAJ; SLJOL